Implementation of the Smart Parking System (SPS): A Study on Cashless Payment for Public Roadside Parking Fees in Surabaya City - Nugroho, Bayu Lukito; Supeno, Eko; Asmorowati, Sulikah; Hapsari, Wundri (Journal of Governance and Administrative Reform, 2024)
Abstract The advancement of Information and Communication Technology (ICT) has revolutionized numerous aspects of life, including urban management, through the adoption of the smart city paradigm. A key initiative within this paradigm is the implementation of a Smart Parking System (SPS), where cashless parking payments play a pivotal role. In 2024, the city of Surabaya introduced a cashless payment system for on-street parking (TJU) as mandated by the Mayor of Surabaya. This study explores and analyzes the development and implementation of the SPS within the framework of TJU parking management policies. A qualitative research method was employed, integrating secondary data analysis, in-depth interviews, and field observations. The analytical framework is based on Weerakkody et al.'s (2011) model, which identifies four critical factors for e-government implementation: political, technological, organizational, and social dimensions. The findings indicate that the cashless parking payment policy has encountered significant implementation challenges. Politically, government support prioritizes fiscal considerations over digital reform in parking management, and communication among stakeholders has been ineffective. Technologically, the integration of the cashless system remains incomplete. Organizationally, the responsibility for transitioning to a cashless system lies with the UPTD Parking Unit of the Surabaya Transportation Agency, which is already burdened with multiple duties, thereby affecting its performance. Socially, the digital divide presents challenges, and public safety concerns arise regarding potential crimes during cashless transactions in on-street parking areas. Moreover, public awareness of the advantages of cashless parking remains low, and the lack of accountability in cash-based transactions has further hindered the acceptance and development of SPS in Surabaya. Keywords: Smart Parking System; Cashless Parking Payment; E-Government; Policy Implementation; Surabaya City Abstrak Perkembangan TIK merubah berbagai aspek kehidupan termasuk tata kelola kota dengan paradigma smart city. Salah satu inisiatif smart city adalah penerapan smart parking system (SPS) dimana aspek pembayaran parkir menjadi komponen penting di dalamnya. Pada tahun 2024, Kota Surabaya menerapkan sistem pembayaran parkir non-tunai di kawasan parkir tepi jalan umum (TJU) berdasarkan instruksi Wali Kota Surabaya. Penelitian ini bertujuan untuk mengetahui dan menganalisis penerapan pengembangan SPS dalam kebijakan tata kelola perparkiran TJU. Penelitian ini menggunakan metode kualitatif yang mengombinasikan eksplorasi data sekunder, wawancara mendalam, dan pengamatan. Teori yang digunakan diadaptasi dari Weerakkody dkk (2011) yang melihat empat faktor kunci implementasi e-government: politik, teknologi, organisasi, dan sosial. Hasil analisis menunjukkan implementasi kebijakan pembayaran parkir non-tunai tidak berhasil dilaksanakan. Secara politik, dukungan pemerintah didasarkan alasan fiskal, bukan reformasi tata kelola parkir berbasis digital. Komunikasi efektif antar stakeholder juga gagal dilakukan. Dari sisi teknologi, integrasi sistem pembayaran parkir non-tunai belum dibangun. Secara organisasi, pelimpahan tanggungjawab transisi sistem pembayaran parkir terletak pada UPTD Parkir Dinas Perhubungan Kota Surabaya. Padahal UPTD Parkir memiliki banyak tupoksi lain sehingga membuat kinerja organisasi menjadi tidak optimal. Secara sosial, isu digital divide perlu mendapatkan perhatian. Selain itu, potensi kejahatan di tepi jalan umum saat melakukan transaksi juga muncul sebagai kekhawatiran masyarakat. Awareness masyarakat terkait manfaat pembayaran parkir non-tunai perlu ditingkatkan. Selain itu, faktor rendahnya akuntabilitas dari pembayaran parkir tunai juga menimbulkan resistensi terhadap pengembangan SPS di Kota Surabaya. Kata kunci: Smart Parking System; Pembayaran Parkir Non-Tunai; E-Government; Implementasi Kebijakan; Kota Surabaya.